(untitled) (Research, Society and Development, 2020)
Among the native palms of the Brazilian Northeast is the Catolé (Syagrus cearensis), whose information about its fruit is incipient. In this way, the objective was to evaluate the physical-chemical characteristics and nutritional quality of the coconut fruit, guaranteeing and expanding its use in the diet of the Brazilian semi-arid region. The whole fruit, the endocarp and the endosperm had an average weight of 39.33; 17.40 and 1.74 g, respectively. In the pulp, the levels of moisture (68.74%), ashes (1.91%), proteins (3.53%), lipids (0.46%) and carbohydrates (25.36%), showed the susceptibility of this fruit to the fungal action, being important to observe its storage conditions. The almond, with low moisture contents (6.51%), showed the protein content (9.95%) and lipid (38.22%), confirming the excellent yield of the genus Syagrus in the production of vegetable oil. For the pulp pigments values of 6.38 and 1.86 mg/100g of total flavonoids and carotenoids were found, respectively. Almond presented a representative profile of minerals: magnesium (143.02 mg/100 g), potassium (515.35 mg/100 g), manganese (2.44 mg/100 g) and copper (1.76 mg/100 g). Most of the daily intake requirements recommended. The study of fruit composition contributes to the knowledge of the nutritional and functional properties of Catolé and to fill a gap still existing in the literature on the potential of using Syagrus cearensis.